2018
DOI: 10.1177/1747021818784403
|View full text |Cite
|
Sign up to set email alerts
|

Higher order affordances for reaching: Perception and performance

Abstract: Affordances are available behaviours emerging from relations between properties of animals and their environment. In any situation, multiple behaviours are available, that is, multiple affordances exist. We asked whether participants could detect means-ends relations among affordances (i.e., higher order affordances) in the context of reaching to a maximum height. We both assessed perceived affordances and evaluated actual reaching ability. In Experiment 1, we co-varied higher order goals (reaching to touch vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Thus, our findings emphasized that irrespective of skill level, climbers were calibrated and therefore affordance perception was scaled to MAC (see Table 3). This finding supports previous research in reaching and grasping, which demonstrates that affordances are scaled to MAC (Pepping & Li, 2000;Wagman & Morgan, 2010), especially when reaching is goal-orientated and combines nested actions (Croft et al, 2018;Pepping & Li, 2008;Wagman et al, 2019). Because calibration of perception-action did not differ with skill level-as also shown for a basic overhead reaching task within climbers (Whitaker et al, 2020)-our study suggests that to improve climbing skill from an intermediate to an advanced level and to perceive new opportunities for action, MAC may need to be enhanced (for similar suggestion, see Knobelsdorff et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, our findings emphasized that irrespective of skill level, climbers were calibrated and therefore affordance perception was scaled to MAC (see Table 3). This finding supports previous research in reaching and grasping, which demonstrates that affordances are scaled to MAC (Pepping & Li, 2000;Wagman & Morgan, 2010), especially when reaching is goal-orientated and combines nested actions (Croft et al, 2018;Pepping & Li, 2008;Wagman et al, 2019). Because calibration of perception-action did not differ with skill level-as also shown for a basic overhead reaching task within climbers (Whitaker et al, 2020)-our study suggests that to improve climbing skill from an intermediate to an advanced level and to perceive new opportunities for action, MAC may need to be enhanced (for similar suggestion, see Knobelsdorff et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with this idea, research has shown that perception of whether an object can be reached depends not only on the fit between arm length and object location but also on the nested context in which that reaching occurs. For example, perception of maximum horizontal reaching distance additionally depends on the posture from which reaching would be performed and the stability of the support surface (Carello, Grosofsky, Reichel, Solomon, & Turvey, 1989;Mark et al, 1997), and perception of maximum vertical reaching distance additionally depends on the means by which reaching would be performed (Wagman, Cialdella, & Stoffregen, 2019;Wagman & Morgan, 2010).…”
Section: Nested Affordancesmentioning
confidence: 99%
“…At every level of the hierarchy, affordances are simultaneously constrained by lower levels (i.e., by lower order affordances or means of performing a given behaviour) but also by higher levels (i.e., higher order affordances or goals for performing a given behaviour). In the context of reaching for an object, affordances for reaching are nested within affordances for maintaining (or changing) posture (i.e., how the reaching is to occur) and the goal of reaching (i.e., why the reaching is occurring; Wagman et al, 2018).…”
mentioning
confidence: 99%